Carcinoma Expleomorphic Adenoma of the Lacrimal Gland. Issue 6 (November 2021) - Vahdani, Kaveh; Rose, Geoffrey E.
Abstract : Aims: To report the characteristics and long-term outcomes of patients presenting with carcinoma ex-pleomorphic adenoma (CXPA) or malignant mixed tumor of the lacrimal gland. Methods: A retrospective case-note review for patients with CXPA, seen at Moorfields Eye Hospital between 1985 and 2018, was performed for demographics, presentation, imaging, histopathology, management, and outcome. Results: Twenty-six patients (11 male; 42%) presented at a mean age of 46 years (median 46.4; range 24–81), with average symptom(s) duration of 67 months (median 24 months; range 6 weeks–53 years). The commonest symptoms were proptosis (13 patients; 50%), orbital ache or pain (11/26, 42%), having noted a lump in the upper eyelid (8/26, 31%), and diplopia (7/26, 27%). About 90% of patients had nonaxial globe displacement, over a half had a palpable mass and 3-quarters had reduced motility. Adenocarcinoma was the commonest malignant component of the tumor, occurring in 16 (62%) of the patients, followed by adenoid cystic carcinoma in 5 patients (19%); 10/26 (28%) tumors showed significant invasion on histological examination. A quarter of the patients had tumor-related death at an average of 2.8 years after diagnosis (median 2.5; range 1.5–4.4 years), and the overall probability of survival for the whole cohort was 63% at both 5 years and 10 years after treatment. The prognosis for CXPA was significantly worse with a history of prior incompletely excised pleomorphic adenoma ( p < 0.001), a markedly invasive malignant component ( p = 0.001), evidence of perineural invasion ( p = 0.042), and an American Joint Committee on Cancer tumor size of T3 or greater ( p = 0.024). Conclusion: Intact excision of CXPAs that do not display histological evidence of extension beyond the tumor pseudocapsule have a good outcome, similar to that for intact excision of benign pleomorphic adenomas. In contrast, our patients with markedly invasive CXPA had a tendency to local recurrence or distant metastasis, and tumor-related death occurred in about two-thirds. Abstract : Two-thirds of our patients with lacrimal carcinomas expleomorphic adenoma displaying local invasion died from the disease, whereas patients with intact excision of tumors with little or no histological evidence of invasion had a good prognosis.